Interaction of Relationship between Job Motivation with Teacher Innovativeness in Improving Education - Henny Suharyati (STKIP Singkawang, 2017)
The purpose of this research is to examine the correlation between dependent variables such as: teacher’s job motivation with an independent variable, innovativeness, of Paud Teachers. The survey is conducted by taking a sample of 144 teachers who had graduated from The Teachers Training College by proportional random sampling technique at Paud teachers in Bogor, West Java, Indonesia. The research used a Sequential Explanatory Design Mixed Method. First the quantitative research is conducted then followed by the qualitative research to support the research has more thoroughly comprehensive output. The quantitative research portrays that there is a very significant positive correlation between the dependent variable with the independent variable. This positive correlation is supported by the qualitative research which states if the dependent variable such as a motivation is higher so independent variable, the innovativeness, will increase too.The quantitative research concludes that: there is a positive correlation between motivation with innovativeness and there are other factors which have a positive correlation in increasing innovativeness. This conclusion is supported by the qualitative research which shows the strongest influence of motivation on innovativeness.